Properties of Titanium Dioxide Nanoparticles Aquesous Dispersions Stabilized By Anionic Surfactants - (:unkn) unknown (My University, 2022)
The stability of titanium dioxide nanoparticles dispersed in aqueous solutions with and without anionic surfactants was investigated as a function of phase separation (sedimentation), particle size at the age of 33 and 303 days, polydispersity at 33 and 303 days, and zeta potential. Mechanical energy in the form of homogenization or mixing with propeller blade mixer was used to wet out the titanium dioxide (TiO2) nanoparticles in the aqueous media and this process was evaluated for the capability of developing a stable dispersion. The ultrasonic waves were used as a second step to form stable dispersions. The research results indicated that the wetting out of the titanium dioxide nanoparticles using homogenization or mixing was not sufficient to develop a stable dispersion, and ultrasonic waves play crucial role in the initial and long-term stability of the dispersions. Furthermore, the effect of nanoparticle dispersion by homogenization or mixing was insignificant when ultrasonic waves were subsequently used. For the dispersed nanoparticles the absolute zeta potential was greater than 30 mV for eleven of the twelve formulas, with -47.40 being the greatest, indicating that a good stability was achieved during the dispersion process. The particle size did not increase significantly for the period from 33 days to 303 days. The polydispersity for all samples was between 0.12-0.23 and 0.13-0.24 at age 33 days and 303 days, respectfully, indicating a moderate polydispersed distribution. The proposed dispersion method demonstrated a pathway for effective dispersion of nanoparticles for application in acidic (pH=4.00-4.10), near-neutral (pH=6.42-6.79), and basic (pH=9.23-10.52) systems.